The relationship between corporate governance structure and family firms' performance. (2015) - Azoury, Nehme; Jreitiny, Richard; Azzi, Georges
The aim of this paper is to highlight how corporate governance (CG) variables affect family firms' performance (FFP). In order to end up with findings, four hypotheses have been set. The first hypothesis indicates that board size affects FFP. The second assumes that correlation exists between duality and FFP. The third suggests that there is a relationship between board composition and FFP. Finally, the fourth hypothesis proposes that chief executive officer (CEO) tenure is related to FFP. Furthermore, in order to test and confirm our hypotheses, a quantitative method has been used to collect our primary data. We accomplished an autopsy by surveying 40 Lebanese family firms through a questionnaire formed by semi-open, closed and multiple choice questions. Out of 40 surveyed Lebanese family businesses, the total number of respondents is 29 and will be subject of our analyses. Moreover, findings have been retrieved and analyses are to be explored via EViews. At last, while concluding this research paper, we determined that there is significant relationship between board size and FFP. Plus, there is strong linkage between duality and FFP. Moreover, there is no degree of association between board composition and FFP. At last, there is no correlation between CEO tenure and FFP.